Decentralized constrained optimal control of the multimachine power system stability improvement - Djibrine Abakar; A A Abouelsoud; Michael Juma Saulo; Simiyu Stanley Sitati (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The paper proposes, a decentralized constrained optimal control of the multimachine power system stability. Today’s power network conditions, operating closer to their limits. Alternative Current power grids are more vulnerable and subject to instability than ever before. A three machine power system and four machines, power system connected with a transmission line lossy. Nonlinear controllers are more complex structure and inflexible to be used in practice paralleled with a linear controller. The linearized dynamical equations of the multimachine power system are near to an equilibrium point and it can be stabilized by using a decentralized constrained controller based on optimal control. The feedback controller, which comprises independent control stations receives the measurement data and influences the control input of the machine is only attached to the subsystems. State feedback controller guarantees the closed-loop system is asymptotically stable can guarantee the performance index. It bases designed controlled systems on the algebraic Riccati equations and all its poles are in the closed left half-plane. Decentralized constrained optimal control of the multimachine power system is achieved through simulation of the results. This achievement of results is proposed by improves power system stability.